Is low-carbohydrate diet score associated with body composition and functional capacity in semi-professional adult soccer players? - Sara Arefhosseini; Mina Araminejad; Helda Tutunchi; Mehrangiz Ebrahimi-Mameghani (BMC Research Notes)
Abstract Objective The present study aimed to determine the link between low-carbohydrate diet score (LCDS), anthropometric indices, and functional capacity in semi-professional soccer players. Methods One hundred nine semi-professional male adult soccer players in Tehran were studied. Anthropometric measures, body composition, serum creatine kinase (CK), and lactate dehydrogenase (LDH) were evaluated. Functional capacity was determined using countermovement jump and Queen’s College step tests. LCDS was estimated using a validated 168-item food frequency questionnaire for each soccer player. Results Mean body mass index (BMI) and fat mass (FM) were 21.86 ± 1.79 kg/m2 and 10.40 ± 4.11%, respectively, while mean LCDS was found 7.43 ± 2.64. Results of functional performance revealed that mean jump height and maximum oxygen consumption were 37.09 ± 4.92 cm and 59.28 ± 42.8 ml/kg/min, respectively. No significant differences in age or BMI were found among LCDS quartiles. Although mean FM in the lowest quartile of the LCDS was lower compared with other quartiles, the differences in FM and fat-free mass were not significant among LCDS quartiles (p > 0.05). Moreover, we failed to observe any associations between LCDS and body composition or functional performance. Conclusion Our results revealed that LCDS was not associated with either body composition or functional capacity in semi-professional male soccer players. Clinical trial number Not applicable.